Water‐Stable DMASnBr3 Lead‐Free Perovskite for Effective Solar‐Driven Photocatalysis - Serena Margadonna (Angewandte Chemie, 2021)
Water-stable metal halide perovskites could foster tremendous progresses in several research fields where their superior optical properties can make differences. In this work we report clear evidence of water stability in a lead-free metal halide perovskite, namely DMASnBr3, obtained by means of diffraction, optical and x-ray photoelectron spectroscopy. Such unprecedented water-stability has been applied to promote photocatalysis in aqueous medium, in particular by devising a novel composite material by coupling DMASnBr3 to g-C3N4, taking advantage from the combination of their optimal photophysical properties. The prepared composites provide an impressive hydrogen evolution rate >1700 μmol g-1 h-1 generated by the synergistic activity of the two composite costituents. DFT calculations provide insight into this enhancement deriving it from the favorable alignment of interfacial energy levels of DMASnBr3 and g-C3N4. The demonstration of an efficient photocatalytic activity for a composite based on lead-free metal halide perovskite in water paves the way to a new class of light-driven catalysts working in aqueous environments.